Dari Muslim Barat Ke Muslim Timur: Tragedi 1453 Sebagai Sebab Awal Aktivitas Maritim Eropa Ke Nusantara - Dadan Adi Kurniawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This paper is a study that focuses on examining the impact of the fall of Constantinople to the Ottoman Turks (1453) on the fate of Muslim society in the archipelago in the following periods. This study uses a historical method consisting of five steps, namely topic determination, heuristics, criticism, interpretation, and historiography. The data collection technique uses historical literature studies in the form of journals, books, theses, articles and videos that are credible and relevant. The results of the study show that the fall of Constantinople (1453) to the Ottoman Turks had an impact on the blockade of the political and economic activities of European nations. The implications are ocean voyages, economic exploration and exploitation, political control and cultural penetration into Asia (including the archipelago). The landscape in the form of seas, coasts and rivers became maritime routes, networks and bridges that supported the realization of economic glory. What Muslim rulers did in the Western world "indirectly" or "unintentionally" influenced the fate of Muslim society in the East due to the arrival and activities of European nations in the archipelago.